2013
DOI: 10.1021/jf400570c
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Chloramphenicol in Crops through Natural Production by Bacteria in Soil

Abstract: Due to the unexpected findings of the banned antibiotic chloramphenicol in products of animal origin, feed, and straw, the hypothesis was studied that the drug is naturally present in soil, through production by soil bacteria, and subsequently can be transferred to crops. First, the stability of chloramphenicol in soil was studied. The fate of chloramphenicol highly depends on soil type and showed a half-life of approximately one day in nonsterile topsoil. It was found to be more stable in subsoil and sterile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 19 publications
(33 reference statements)
0
32
0
3
Order By: Relevance
“…Nevertheless, illegal usage of CAP drug still continues in the lowincome areas, owing to its low cost and easy availability. Many previous reports showed that the ingested CAP could not be completely metabolized, and a relatively high proportion of parent drug were discharged into aquatic environment through the excrement [4,5]. As a result, CAP has been frequently determined in many waters [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, illegal usage of CAP drug still continues in the lowincome areas, owing to its low cost and easy availability. Many previous reports showed that the ingested CAP could not be completely metabolized, and a relatively high proportion of parent drug were discharged into aquatic environment through the excrement [4,5]. As a result, CAP has been frequently determined in many waters [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting these observations on the occurrence of antibiotics in natural environments, Berendsen et al. () recently observed a high production of the antibiotic compound chloramphenicol by a population of added soil bacteria.…”
Section: Do Antibiotics Cause Predation In Pristine Natural Environmementioning
confidence: 92%
“…In many studies on antibiotic degradation in the environment, it was impossible to distinguish between the rate of biotic and abiotic degradation. However, an experiment comparing degradation of chloramphenicol in sterilized vs unsterilized soil convincingly showed the major role of the native microbial population in the degradation of this antibiotic residue (Berendsen, 2013). The extent, kinetics and process of degradation are mainly influenced by physicochemical properties of antibiotics such as structure, concentration, solubility, adsorption ability to soil, fixation ability to pores of soil matrix, and by environmental conditions, such as temperature, rainfall, and humidity (Tolls, 2001;Halling-Sørensen, 2002;Sarmah, 2006).…”
Section: Degradation (Transformation)mentioning
confidence: 99%
“…Apart from their effects on soil microbial communities, the presence of antibiotic residues in the environment has also repeatedly been show to result in residues in crops (Kumar, 2005b;Dolliver, 2008;Bassil, 2013;Chitescu, 2013;Berendsen, 2013).…”
Section: Effect On Microbial Communitiesmentioning
confidence: 99%